Understanding nurses perspectives of acuity in the process of emergency mental health triage: a qualitative study. Issue 3 (3rd May 2020) - Broadbent, Marc; Moxham, Lorna; Dwyer, Trudy
Abstract : Background: Post deinstitutionalisation, mental health mainstreaming has led to substantial increases in presentations to Emergency Departments (EDs). The assessment process requires the ED triage nurse to undertake a rapid client assessment, assign a clinically appropriate triage score, and then refer the client to a mental health clinician. The initial assessment is important, and a number of factors influence the process of triage, referral and response including an understanding of mental health presentation acuity. Aim: To understand the factors that influence the ED triage assessment, referral and clinical response of clients with a mental illness. Methods: An ethnographic methodology underpinned the research design. ED triage nurses and mental health triage nurses who worked in a regional hospital provided insights through interviews and observations. The study was also informed by institutional policies and procedures regarding triage. Transcribed in-depth interviews, field notes and memos were analysed using an inductive thematic process. Findings: Mental health triage nurses and ED triage nurses concur that triage is an important part of the assessing process for a person who presents to the ED with a mental health problem. Timely and clinically accurate assessment, followed by referral and response is strongly influenced by the user knowledge of the mental health triage scale, and comprehension of mental health acuity. The conflicting understandings between the two professional nursing groups, called professionally cultured orientations, further impact this process. Conclusion: Professionally cultured orientation to mental health triage and acuity comprehension influence the process of emergency mental health triage and therefore may affect optimal client outcomes. Further research into ED triage design, ED triage education, and a shared understanding of acuity is called for.